Inclusion of zeolitic imidazolate framework-8 (ZIF-8) crystals within porous polyether sulfone (PES) via filtration methods as potential electrolytes for DMFC applications - Junoh, H. (Elsevier Ltd, 2020)
The imidazolate framework-8 (ZIF-8) crystals were synthesized by in -situ growth techniques inside the pore of porous poly ether sulfone (PES) in order to fabricate a composite PES/ZIF-8 electrolyte membrane for direct methanol fuel cell (DMFC) applications. In situ techniques by adapting the filtration method was adhered in this study. It was found that the proton conductivity (17.9 Ã 10-3Scm-1) was drastically increased for PES/ZIF-8 as compared to pristine PES membrane (0.21 Ã 10-3Scm-1). However, the methanol barrier property was slightly decreased from 2.07 Ã 10-7cm2s-1to 3.88 Ã 10-7cm2s-1for PES and PES/ZIF-8 membranes, respectively. The introduction of ZIF-8 in PES membranes not only improve proton conductivity, but also positively affected the mechanical stability of PES/ZIF-8 with 1.73-fold lower of swelling ratio even though the water uptake increased by 2.08 folds. In spite of the increment in methanol permeability, selectivity of PES/ZIF-8 membrane was 6 folds and 2 folds higher than pristine PES and NafionÂ®, respectively which indicated that the potential for PES/ZIF-8 to be a good candidate for electrolyte in DMFC applications. Nonetheless, via scanning electron microscopy (SEM) showed a good distribution of ZIF-8 crystals inside the pore of PES membranes which proven that the effectiveness of filtration techniques for ZIF-8 crystals in-situ growth synthesized within the pores. Â© 2020 Elsevier Ltd. All rights reserved.